Efektivitas Gaya Kepemimpinan, Kompetensi, Dalam Rangka Meningkatkan Kinerja Aparatur Yang Dimediasi Oleh Komitemen (Studi Pada Aparatur Kecamatan Karang Penang Kabupaten Sampang) - Mahrudi Mahrudi; Hadi Susanto; Sri Mulyani (Universitas 45 Surabaya, 2023)
Mahrudi, 2023. The Effectiveness of Leadership Style, Competence, in the Order of Improving Apparatus Performance Mediated by Commitment, Wijaya Putra University Postgraduate Program. This type of research is explanatory, namely to test the hypotheses between the hypothesized variables that will be tested for truth. by using a quantitative approach, the research sample was 42 respondents. In this study the data will be processed using SEM-PLS data analysis. The aims of this study are: 1) To describe the leadership style, competence, commitment and performance of the apparatus. 2) To test and analyze the influence of leadership style on apparatus performance. 3) To examine and analyze the influence of leadership style on apparatus commitment. 4) To test and analyze the effect of competency on device performance. 5) To test and analyze the influence on apparatus commitment. 6) To test and analyze the influence on apparatus performance. 7) To examine and analyze the indirect influence of leadership style on apparatus performance mediated by Commitment. 8) To examine and analyze the indirect effect of competence on apparatus performance which is mediated by Commitment. The results of the study show that: 1) Leadership style has no significant effect on apparatus performance. 2) Leadership style has a significant effect on attention. 3) Competence has no significant effect on device performance. 4) Competence has a significant effect on attention. 5) Commitment has a significant effect on apparatus performance. 6) Leadership style has no significant effect on apparatus performance which is mediated by commitment. 7) Competence has a significant effect on the performance of the apparatus which is mediated by the liver.